Role of Microfinance to Alleviate Poverty in Pakistan - Arslan Elven; Dr. Sohaib Uz Zaman (Indus Journal of Social Sciences, 2025)
Microfinance has been economic driver for many countries and helps in building economy and prosperity. While number of banks and MFIs has been working in Pakistan yet a there is a stagnant growth in economy. The purpose of this study is to analyze the role of microfinance on poverty alleviation, Microfinance directly affects socio economic factors such as income generation, Health facilities access to education as well as entrepreneurial and employment opportunities. This study evaluates whether microfinance plays a crucial role in empowering individuals in their financial matters and also it aims to provide insights into its contribution to poverty alleviation.